(untitled) (Research, Society and Development, 2022)
Objective: To describe epidemiological aspects and the evolution of HIV infection among indigenous people in the southern region of the state of Mato Grosso do Sul. Method: Cross-sectional, descriptive and retrospective study, based on records from the Notifiable Diseases Information System in the years 2005 -2018. Data from individuals aged 13 years and over, from the indigenous population assisted by the Special Indigenous Health District of the Japorã Base Pole and diagnosis with HIV/AIDS infection, were transferred to a comparison spreadsheet with the local information system. To calculate the prevalence and evolution of cases, the annual number of new HIV/AIDS cases was used. Results: 17 (65.4%) cases were identified in women, 13 (72.2%) between 20-39 years. Five (19.2%) developed AIDS. The HIV/AIDS detection rates for the years 2016 and 2018 were 115.54 and 155.49 respectively. HIV prevalence rates fluctuated between the years 2016, 217 and 218. The Porto Lindo village had a detection rate of 59.878/100 thousand inhabitants, Yvykatu 400.802/100 thousand inhabitants and Pyelito Kuê 602.409/100 thousand inhabitants. The AIDS death rate in the Porto Lindo village was 2.24/10 thousand inhabitants and 40.08/10 thousand inhabitants in Yvykatu. The abandonment rate for the Porto Lindo village was 6.73/10 thousand inhabitants. Conclusion: HIV detection rates tended to increase in the indigenous people studied. It is necessary that studies be carried out to direct actions that impact the infection prevalence indicators.